2001
DOI: 10.1093/intqhc/13.5.375
|View full text |Cite
|
Sign up to set email alerts
|

Asthma care and factors affecting medication compliance: the patient's point of view

Abstract: The factors of importance for self-reported compliance with prescribed medication were age, gender, duration of the disease, the attitude of the staff and information/education about asthma. The patients expressed important aspects of care, and these are in accordance with how an asthma nurse practice functions in Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 7 publications
2
41
0
1
Order By: Relevance
“…3,16 If the patients are ignorant or have a partial knowledge of their disease and treatment then this can lead to poor compliance. 17,18 The present study reveals that the patients' specific knowledge on asthma is low; however, the patients had positive attitude towards their disease. Our results were similar in pipeline as reported by others.…”
Section: Discussionmentioning
confidence: 57%
“…3,16 If the patients are ignorant or have a partial knowledge of their disease and treatment then this can lead to poor compliance. 17,18 The present study reveals that the patients' specific knowledge on asthma is low; however, the patients had positive attitude towards their disease. Our results were similar in pipeline as reported by others.…”
Section: Discussionmentioning
confidence: 57%
“…More time increases the possibilities for each patient to receive time for individual needs, which may enable patients to become more aware of the signs and symptoms of the disease. [19][20][21][22][23] It also enables the nurse and the patient to create a self-management plan, including adjustment of medication in different situations, which may result in more adequate treatment and enhanced asthma control. [24][25][26] In Sweden, time allocation for the asthma nurse is a problem in most cases, 10 which undoubtedly influences the quality of the work performed at the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have shown that guidelines are slowly implemented in healthcare systems [4] and that there is substantial room for improvement with respect to the prescribing doctors' adherence to guidelines [56][57][58][59] as well as patient compliance [60][61][62].…”
Section: Regional Variations and Adherence To National Guidelinesmentioning
confidence: 99%